The Meaning of Digital Literacy in the Life of Teenagers (Case Study of Adolescents in RT 021 RW 006 Talang Kemang Gandus Palembang) - Mardiah, Annisatul; Nirmala, Sila (Sinergi International Journal of Communication Sciences, 2025)
This study analyzes the meaning of digital literacy in adolescents living in RT 021 RW 006 Talang Kemang Gandus, Palembang. Qualitative case study designs were applied to explore how adolescents build, practice, and experience digital literacy in their daily lives. Data were collected through in-depth interviews, participatory observations, and documentation, then analyzed thematically using the Braun & Clarke approach. The findings show that adolescents are actively using digital media, especially WhatsApp, TikTok, Instagram, and YouTube, to meet communication, entertainment, and academic needs. Digital literacy practices are influenced by social environment, family, access to technology, gender, and type of school. Although adolescents are categorized as digital natives, their critical literacy skills are still underdeveloped, making them vulnerable to misinformation. Theoretically, this research refers to critical digital literacy, use and satisfaction, and digital capital. Practically, there study recommends strengthening family involvement, integrating essential digital literacy into school curricula, and designing government policies that are responsive to the needs of youth in urban areas.